IMPROVING THE UNDERSTANDING CONCEPT OF LOCAL WISDOM BASED ON PROBLEM-BASED LEARNING: TEACHING MATERIALS “LENTERA” IN ELEMENTARY SCHOOL - Silvi Fatimah Azhara Suherman; Mubarok Somantri; Non Dwishiera Cahya Anasta Shiera (El Midad, 2025)
This study is motivated by fourth-grade students who have difficulty understanding the concept of IPAS, especially in local wisdom material. Based on the observation of the lack of teaching materials that support learning and teacher-centred learning methods. The purpose of this research is to develop PBL-based "LENTERA" teaching materials that can improve the understanding of grade IV elementary school students regarding local wisdom material. This research employs the Design and Development (D&D) methodology with the ADDIE model, which includes the Analysis, Development, Implementation, and Evaluation stages. The results of this study indicate that teaching materials are very feasible to use, with material experts getting a percentage of 95% very feasible category, design experts getting a percentage of 95% very feasible category, and learning practitioners getting a percentage of 92.5% in % very feasible category based on the results of limited trials of grade IV elementary school students. This study concludes that PBL-based “LENTERA” teaching materials are highly effective for grade IV elementary school students in understanding the concept of local wisdom material.